Skeletonization of the radial artery: advantages over the pedicled technique. - Taggart, D; Mathur, M; Ahmad, I (2001)
The radial artery is usually harvested as a pedicle with surrounding veins, perivascular fat, and areolar tissue. We describe an alternative technique of skeletonization of the radial artery and its potential advantages over the pedicled technique.